Nauka o wcieleniu Słowa u św. Hilarego z Poitiers - Kołosowski, Tadeusz (Vox Patrum, 2000)
The author of the article presents the teaching of Saint Hilary about Incarnation of Christ and how bishop of Poitiers understands: the form of God and form of servant, the eternal birth of Word by Father, the real Deity and human nature of Christ, the question of soul human and body of Christ, the unity of Word Incarnate and the meaning of Incarnation's mystery.